Cosmetic Treatments with Energy-Based Devices in Skin of Color - Chao, Janet Ren; Porter, Jennifer Parker; Hessler, Jill (Facial Plastic Surgery, 2023)
The use of energy-based devices in cosmetic treatments for patients with higher Fitzpatrick skin types is a topic of concern due to the increased risk of complications such as hyperpigmentation and scarring. Advancements in technology have enabled the development of safe and effective energy-based modalities for improving skin tone, texture, and signs of aging in patients with higher Fitzpatrick skin types. This article reviews various modalities that have shown positive outcomes in Fitzpatrick skin types 4 to 6.Radiofrequency (RF) skin tightening devices have emerged as a noninvasive method for improving skin laxity by stimulating collagen and elastin production without generating excessive heat, making them suitable for darker skin tones. Microfocused ultrasound (MFUS) is another noninvasive option for skin tightening and lifting. By producing thermal coagulation in the deeper layers of the skin, MFUS stimulates collagen production, resulting in improved skin tightness. Fractional laser resurfacing, both ablative and nonablative, offers effective treatment options for various concerns such as acne scars, skin texture, and dyspigmentation. Nonablative fractional lasers, which target water rather than melanin, are particularly safer for darker skin types. Broadband light devices that emit different wavelengths have shown success in skin rejuvenation, improving wrinkles, pore size, erythema, telangiectasias, and dyspigmentation. Additionally, RF microneedling combines the benefits of both modalities, delivering safe treatment for skin laxity and textural concerns. The short-pulse neodymium-doped yttrium aluminum garnet (Nd:YAG) laser has become a transformative tool for patients with Fitzpatrick skin types 4 to 6. This laser targets melanin, hemoglobin, and water, providing improvements in hyperpigmentation, acne, fine lines, and scar texture. Combining the short-pulse Nd:YAG laser with other treatments like chemical peels or microneedling has shown synergistic effects and enhanced outcomes. Understanding these modalities and tailoring treatments to specific concerns is crucial for safe and effective solutions in patients with higher Fitzpatrick skin types.
Keywords: energy-based devices; Fitzpatrick skin types; skin of color; hyperpigmentation; skin rejuvenation